Place of birth for unintended pregnancies in six former Soviet Union countries. (6th May 2021) - Bellizzi, Saverio; Pichierri, Giuseppe; Panu Napodano, Catello M; Murgia, Paola; Padrini, Susanna; Bassat, Quique
Abstract: Objective: This paper aims at exploring the association between unintended pregnancies and place of birth in six Former Soviet Union (FSU) countries. Material and methods: A secondary analysis of the latest cross‐sectional Demographic and Health Surveys of six FSU countries from 2005 through 2012 was conducted. Prevalence of institutional births and unintended pregnancies was estimated by country and for the pooled population. Odds ratio (OR) and 95% confidence interval (CI) were calculated to measure the country and pooled association between pregnancy intention and institutional birth. Results: Institutional births occurred in 90.4% of the overall study population and ranged from 78.2% in Tajikistan to 99.7% in Ukraine Demographic and Health Survey. Around one out of 10 pregnancies resulted unintended. In the pooled analysis, unintended pregnancies were significantly associated with giving births outside health facility (aOR1.2; 95% CI 1.0–1.6). Conclusion: Based on the study findings we suggest that increase awareness of benefit of skilled delivery care is needed among women with poor access to family planning.